2020
DOI: 10.3390/pathogens9050397
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation and Characterization of Chryseobacterium cucumeris SKNUCL01, Isolated from Diseased Pond loach (Misgurnus anguillicaudatus) in Korea

Abstract: Loaches are widely distributed throughout the natural environment and are consumed for medicinal purposes in East Asia. Usually, loaches are cultured in ponds where the water conditions can easily cause bacterial infections. Infections due to bacterial pathogens such as Aeromonas have been well described in cultured loaches; however, there is no report regarding Chryseobacterium infection. This study focused on the elucidation of the pathogenic and antibiotic resistance characteristics of C. cucumeris, SKNUCL0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the case of the present study, the pathogenesis of Chryseobacterium was presumed to proceed from a localized to a systemic infection. It was also observed in our previous report with C. cucumeris [32]. Furthermore, considering the production of proteolytic enzymes, including esterase, the zoonotic potential of C. balustinum through infection through the skin should not be excluded.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the case of the present study, the pathogenesis of Chryseobacterium was presumed to proceed from a localized to a systemic infection. It was also observed in our previous report with C. cucumeris [32]. Furthermore, considering the production of proteolytic enzymes, including esterase, the zoonotic potential of C. balustinum through infection through the skin should not be excluded.…”
Section: Discussionmentioning
confidence: 59%
“…Since, Chryseobacterium sp. has been recognized as an emerging fish pathogen in South Korea in recent times, studies regarding antibiotic susceptibility-based treatment methods should precede [32,37]. In a previous Chryseobacterium infection case study, we failed to cure the diseased fish and we speculated that high prevalence of antibiotic resistance by Chryseobacterium was a reason.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…MKAL5 displayed moderate ability. Many investigators revealed the biofilm-forming ability of these bacteria species [Esteban and García-Coca, 2018;Kim et al, 2020;Bostanghadiri et al, 2021;Sornchuer et al, 2022]. Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Before collecting samples from the animals, either anesthesia was induced or euthanasia was performed with tricaine mesylate, as described previously [ 26 ]. Blood was collected from the caudal vein, and the spleen was collected from the aseptically opened peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%